Anti-Corruption Values Potrayal in English Textbooks for Senior High School Grade XII: Critical Discourse Analysis Perspective - Prayogo Hadi Sulistio; Erna Wardani (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
This study is aimed to investigate anti-corruption values portrayal in English textbooks for senior high school grade XII. This research used content analysis. Data collection was carried out by determining anti-corruption values which were divided into three, namely: core values, attitude values and work ethic values then grouping reading texts, dialogues and illustrations representing the three anti-corruption values and interpreting the implementation of anti-corruption education according to the data found. The results of this study indicate that the coverage of anti-corruption values in textbooks dominantly present honesty, care and hardworking values in dialogues, reading texts and illustrations. Furthermore, anti-corruption values are represented by various expressions such as caring, empathy, responsibility in various contexts not only to increase students' interpersonal skills, but also to apply anti-corruption values that the students find in dialogues, reading texts, and illustrations in daily life. It shows that the authors of the textbooks have tried to insert anti-corruption values as part of anti-corruption education initiated by the Corruption Eradication Commission in collaboration with the government